2019
DOI: 10.1177/1120672119833896
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis associated with fungal keratitis and penetrating injuries in North China

Abstract: Purpose: To report the laboratory findings, management strategies, and visual outcomes of culture-proven exogenous fungal endophthalmitis in North China. Methods: The microbiological and treatment records of patients with culture-positive exogenous fungal endophthalmitis who visited the Affiliated Hospital of Qingdao University from January 2012 to December 2016 were reviewed. Results: A total of 39 eyes (39 patients) were identified over a 5-year period. Exogenous fungal endophthalmitis was associated with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Our results indicate that penetrating objects can cause fungal endophthalmitis, with plant material and iron objects being the predominant causes. As in previous studies [ 6 8 ], we observed a latent period of fungal endophthalmitis after a penetrating ocular trauma. The onset of fungal endophthalmitis after trauma was usually subacute or chronic.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results indicate that penetrating objects can cause fungal endophthalmitis, with plant material and iron objects being the predominant causes. As in previous studies [ 6 8 ], we observed a latent period of fungal endophthalmitis after a penetrating ocular trauma. The onset of fungal endophthalmitis after trauma was usually subacute or chronic.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of posttraumatic fungal endophthalmitis varies in different countries. Fungal endophthalmitis after trauma predominantly occurs in developing countries, such as India and China [ 6 8 ], but it is rare in developed countries. A report from the USA retrospectively reviewed 41 cases of fungal endophthalmitis over 16 years, which included just 10 cases of posttraumatic fungal endophthalmitis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Attention should be paid to the rational use of topical antiviral drugs. Anti-fungal drugs were seldom used, which was in accordance with the low prevalence of diagnosed ocular fungal infection [ 35 ]. Moreover, oral formulations and off-label use of injectable formulations are often used, but were not included for analysis in this study [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of evisceration and poor visual outcomes have been reported in cases with Aspergillus spp. growth 20,28,33 . Some of the risk factors associated with enucleation/evisceration include endophthalmitis secondary to corneal ulceration or endogenous endophthalmitis and initial poor VA 29 .…”
Section: Discussionmentioning
confidence: 99%